Bifunctional chelators in the design and application of radiopharmaceuticals for oncological diseases - Sarko, Dikran; Eisenhut, Michael; Mier, Walter; Haberkorn, Uwe (Current medicinal chemistry, 2012)
Abstract: Radiopharmaceuticals constitute diagnostic and therapeutic tools for both clinical and preclinical applications. They are a blend of a tracer moiety that mediates a site specific accumulation and an effector: a radioisotope whose decay enables either molecular imaging or exhibits cytotoxic effects. Radioactive halogens and lanthanides are the most commonly used isotopes for radiopharmaceuticals. Due to their ready availability and the facile labeling metallic radionuclides offer ideal characteristics for applications in nuclear medicine. A stable link between the radionuclide and the carrier molecule is the primary prerequisite for in vivo applications. The radionuclide is selected according to its physical and chemical properties i.e. half-life, the type of decay, the energy emitted and its availability. Bifunctional chelating agents are used to stably link the radiometal to the carrier moiety of the radiopharmaceutical. The design of the bifunctional chelator has to consider the impact of the radiometal chelate on the biological properties of the target-specific pharmaceutical. Here, with an emphasis on oncology, we review applications of radiopharmaceuticals that contain bifunctional chelators, while highlighting successes and identifying the key challenges that need to be addressed for the successful translation of target binding molecules into tracers for molecular imaging and endoradiotherapy.